PENEGAKAN HUKUM PIDANA PENYALAHGUNAAN NARKOTIKA SEBAGAI PELAKU PENGEDAR - Ohoiwutun, Machita Mariane; Soekorini, Noenik (Yustitia, 2024)
Enforcement of criminal law against drug abuse by traffickers is a crucial issue that continues to receive attention from the government and society. This research aims to analyze the monitoring mechanisms applied to drug abuse cases, especially if they involve drug dealers. The methodology used in this research includes a normative legal approach with analysis of applicable laws and regulations, as well as case studies of related court decisions. The survey results show that although various law enforcement efforts have been carried out, there are still several challenges that hinder their effectiveness, such as limited law enforcement resources and lack of coordination between related institutions. This study recommends increasing training and law enforcement capacity, as well as increasing cooperation between agencies to strengthen efforts to eradicate drug trafficking. It is hoped that this research can contribute to improving the criminal law enforcement system in Indonesia, especially in handling drug addiction cases.